Challenges in efficacy research: the case of feeding alternatives in patients with dementia. (25th February 2014) - Zapka, Jane; Amella, Elaine; Magwood, Gayenell; Madisetti, Mohan; Garrow, Donald; Batchelor‐Aselage, Melissa
Abstract: Aims: To explore factors at the family caregiver and nursing home administrative levels that may affect participation in a clinical trial to determine the efficacy of hand feeding vs. percutaneous gastrostomy tube feeding in persons with late‐stage dementia. Background: Decision‐making regarding use of tube feeding vs. hand feeding for persons with late‐stage dementia is fraught with practical, emotional and ethical issues and is not informed by high levels of evidence. Design: Qualitative case study. Methods: Transcripts of focus groups with family caregivers were reviewed for themes guided by behavioural theory. Analyses of notes from contacts with nursing home administrators and staff were reviewed for themes guided by an organizational readiness model. Data were collected between the years 2009–2012. Results: Factors related to caregiver willingness to participate included understanding of the prognosis of dementia, perceptions of feeding needs and clarity about research protocols. Nursing home willingness to participate was influenced by corporate approval, concerns about legal and regulatory issues, and prior relationships with investigators. Conclusion: Participation in rigorous trials requires lengthy navigation of complex corporate requirements and training competent study staff. Objective deliberation by caregivers will depend on appropriate recruitment timing, design of recruitment materials and understanding of study requirements. The clinical standards and policy environment and the secular trends there‐in have relevance to the responses of people at all levels.